Semantic-Structural Classification of Aphorisms and Quotations - Khasanovna, Ganieva Dilafruz; Xusnida, Bozorboyeva (European Journal of Life Safety and Stability (2660-9630), 2022)
The article is devoted to the study of semantic-structural classification of aphorisms and quotations in the English language. It was the subject of deep study of scientists in most different ideological branches. Most of the scientists agreed that aphorisms and quotations give emotionality, expressiveness to the speech, where was not only the person's point of view, but also general people's outlook is expressed. Aphorisms and quotations play important role in language.